How would you solve this for x?

(5x² + 6x)(12x² - 5x - 2) = 0

(5x² + 6x)(12x² - 5x - 2) = 0

5x² + 6x = 0 or 12x² - 5x - 2 = 0 {set each factor equal to 0}

x(5x + 6) = 0 or (4x + 1)(3x - 2) = 0 {factored x out of 1st and factored 2nd into two binomials}

x = 0 or 5x + 6 = 0 or 4x + 1 = 0 or 3x - 2 = 0 {again, set each factor equal to 0}

x = 0 or 5x = -6 or 4x = -1 or 3x = 2 {started solving each equation for x}

**x = 0 or x = - 6/5 or x = -1/4 or x = 2/3**{solved each equation for x}

*© Algebra House*